Investigation of the Youth’s Social Relationships and Their Interactions in Park (Case Study: Amol City) - beheshteh mohammadi; mahmoud sharepour (توسعه اجتماعی)
Social relationship is one of the most important factors in satisfying people’s needs. The purpose of this article is to investigate individuals’ social relationships in park. This is a survey research and the population includes all the youth aged from 15-29 in Amol and 300 youth in this city were chosen as the sample of the study. A questionnaire was administered by the researchers to collect data. Findings of the research show that there is significant difference between the measuring variables. Investigation of background variables such as gender, age, education, marital status, and occupation shows a significant difference between gender and social relationships in park space in that way boy enjoy more social relationship. The relationship between education and social relationship was significant in that people with higher levels of education bear less social relationship. Age also had a significant relationship with social relationships in park space. Five independent variables were also measured with social relationship in this research, including socio-economic base, cultural capital, social capital, spatial desirability, and the extent to which space is used. It was found that the most important factor in building social relationships in park space was having a high social capital.